Statin therapy in athletes and patients performing regular intense exercise – Position paper from the International Lipid Expert Panel (ILEP). (May 2020) - ; Alnouri, Fahad; Amar, Fahma; Atanasov, Atanas G.; Bajraktari, Gani; Banach, Maciej; Bartlomiejczyk, Marcin A.; Bjelakovic, Bojko; Bruckert, Eric; Bielecka-Dabrowa, Agata; Cafferata, Alberto; Ceska, Richard; et al.
Abstract: Acute and chronic physical exercises may enhance the development of statin-related myopathy. In this context, the recent (2019) guidelines of the European Society of Cardiology (ESC) and the European Atherosclerosis Society (EAS) for the management of dyslipidemias recommend that, although individuals with dyslipidemia should be advised to engage in regular moderate physical exercise (for at least 30 min daily), physicians should be alerted with regard to myopathy and creatine kinase (CK) elevation in statin-treated sport athletes. However it is worth emphasizing that abovementioned guidelines, previous and recent ESC/EAS consensus papers on adverse effects of statin therapy as well as other previous attempts on this issue, including the ones from the International Lipid Expert Panel (ILEP), give only general recommendations on how to manage patients requiring statin therapy on regular exercises. Therefore, these guidelines in the form of the Position Paper are the first such an attempt to summary existing, often scarce knowledge, and to present this important issue in the form of step-by-step practical recommendations. It is critically important as we might observe more and more individuals on regular exercises/athletes requiring statin therapy due to their cardiovascular risk.